The Differences in the Safety and Tolerability of Immune Checkpoint Inhibitors as Treatment for Non–Small Cell Lung Cancer and Melanoma: Network Meta-Analysis and Systematic Review - Chai, Qing-Qing; Du, Jiang-Yang; Zhu, Jun; Wu, Bin (Frontiers in Pharmacology, 2019)
Background: Immune checkpoint inhibitors (ICIs) have made an evolvement for the treatment in solid tumors. Besides the efficacy of ICIs for cancer disease, the adverse events are also noteworthy in the gradually extensive clinical use. Objective: To make a systematic review and network meta-analysis to evaluate the treatment-related AEs occurred in the clinical trials when using different kind of ICIs. To explore the AEs differences among ICIs in treating NSCLC and melanoma. And make a comparison in selected immune-related AEs. Methods: PubMed, Embase, Cochrane Library, ClinicalTrials.gov and other available sources were systematically searched for the published reports due to January 1, 2019. Two reviewers independently selected the reports about phase II/III RCTs for the comparison between ICIs or ICIs and chemotherapy. After the assessment on bias of all-included trials, a Bayesian network meta-analysis was performed. Primary outcomes were any grade and high-grades treatment-related AEs based on all ICIs. Secondary outcomes were AEs in NSCLC and melanoma, and the selected pneumonitis/ pneumonia and colitis. Results: 18 RCTs containing 11,223 patients with NSCLC or melanoma were included. A total network meta-analysis was conducted, and it showed that in all inventions, atezolizumab 1200mg and pembrolizumab 2mg/kg every 3 weeks were ranked as more tolerable in general. Combined ICI with chemotherapy might suggest a higher risk of treatment-related AEs than monotherapy of ICIs not including durvalumab or ipilimumab. In the subgroup of NSCLC, pembrolizumab was related with higher risk of high-grades AEs than nivolumab, and ICIs (nivolumab, atezolizumab and avelumab) led to a lower risk of any/high-grades treatment-related AEs than traditional chemotherapy and ICI combined chemotherapy. But ICIs did not present safety or tolerance than chemotherapy in treating melanoma. Pneumonitis/ pneumonia was considered pertinent with nivolumab, durvalumab, 2 ICIs and ICI combined chemotherapy, but ICIs did not distinguish significantly in pneumonitis/ pneumonia when treating NSCLC. Combined nivolumab and ipilimumab was ranked highest risk in colitis, while pembrolizumab and atezolizumab had a lower possibility. Conclusion: atezolizumab 1200mg and pembrolizumab 2mg/kg every 3 weeks were ordinarily safer. When treating NSCLC, nivolumab had the lowest risk, and pembrolizumab had lowest toxicity in melanoma.